Perilaku Masyarakat Pesisir Terhadap Pengelolaan Sampah Plastik di Kelurahan Tanjung Unggat Kota Tanjungpinang - Putri Amelia Febrianty; Erpina Santi Meliana Nadeak; Harvensica Gunnara; Luh Pitriyanti (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2025)
Background: Plastic waste pollution in coastal areas, primarily caused by direct disposal into the sea without proper management, has serious consequences for both the environment and coastal communities. This research seeks to assess respondents’ knowledge, attitudes, and behavioral practices related to the management of household plastic waste in the coastal area of Tanjung Unggat Subdistrict. Methods: This research employed a descriptive cross-sectional design using survey and interview methods. The sampling technique applied was total sampling, encompassing the entire population of 41 housewives. The study was conducted in RT 02 RW 05, Tanjung Unggat Subdistrict, Bukit Bestari District, Tanjungpinang City, Indonesia. Data were analyzed using descriptive statistical methods. Results: The findings revealed that 92.7% of respondents demonstrated a high level of knowledge regarding household plastic waste management. In terms of attitudes, 87.8% of respondents expressed agreement with household plastic waste management practices. However, in the aspect of practice, 68.3% of respondents were categorized as having low implementation levels in managing household plastic waste. Conclusion: This study highlights a clear gap between respondents’ adequate knowledge and positive attitudes, and their relatively low levels of actual practice. These findings suggest the need for more intensive educational interventions to promote behavioral change in household plastic waste management.